S28 Clinical predictors of admission in infants with acute bronchiolitis. (16th November 2010) - Marlais, M; Evans, J; Abrahamson, E
Abstract : Introduction: Bronchiolitis is a significant cause of acute morbidity in the first 12 months of life. A proportion of infants will be admitted to hospital and currently the decision to admit is based on clinical judgement alone. Research evidence identifying indicators for admission is scarce, there have been no studies assessing clinical predictors of admission in infants with bronchiolitis under the age of 12 months. Aim: To determine which clinical features in the emergency department are able to predict the need for hospital admission in infants with acute bronchiolitis. Methods: All infants presenting with acute bronchiolitis to one tertiary paediatric emergency department from April 2009 to March 2010 were included in this study. Inclusion criteria were a clinical diagnosis of bronchiolitis in an infant aged <12 months. The case notes for each infant were reviewed and data on 29 potential clinical predictors were recorded. An exhaustive list of potential clinical predictors was devised through literature review. Institutional approval was obtained to perform this study. Logistic regression analysis was performed to determine which clinical features could predict admission. Results: 449 infants presented with acute bronchiolitis during the study period (298 (66%) male, mean age 23±14.5 weeks). 163 (36%) infants were admitted to hospital. The main clinical features predictive of admission (mean for admitted group vs discharged group respectively) included: younger age at presentation (mean 17.9 weeks vs 26.4 weeks, p<0.001), higher respiratory rate (mean 54.6 vs 46.9, p<0.001), higher heart rate (mean 162.8 vs 147.7, p<0.001), lower oxygen saturation (mean 96.4% vs 98.4%, p<0.001), lower duration of symptoms (mean 2.9 days vs 4.9 days, p<0.001), lower weight at presentation (mean 6196 g vs 7897 g, p<0.001). The best single predictor of admission was oxygen requirement in the emergency department (OR 78.4 (95% CI 18.8 to 326.9), p<0.001). Conclusion: We have identified seven objective clinical parameters which can be used in the emergency department to predict which infants with bronchiolitis require admission to hospital. These data have been assimilated into a simple clinical risk score; further work is required to validate this scoring system and to assess its utility in supporting clinical decisions.